2011
DOI: 10.1002/cpp.785
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Exploration of Empowerment from the Perspective of Young People with Psychosis

Abstract: The way practitioners interact with young people impacts upon their experience of empowerment. Young people with psychosis equate being listened to with being empowered. Young people with psychosis, especially when hospitalized, want to develop and use their own coping styles. Clinicians who give choices and have a sense of humour are valued by young people with psychosis. Clinicians must consider whose needs are being met when decisions are made for young people with psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(92 citation statements)
references
References 32 publications
5
85
0
2
Order By: Relevance
“…Recent literature emphasises the importance of empowerment in helping patients take charge of their own life and making decisions on their own (Grealish, Tai, Hunter, & Morrison, 2011). This is in line with the present study where the experience of being listened to and being able to talk about their experiences is viewed by patients as being positive and helpful in the healing process.…”
Section: Knowledge and Educationsupporting
confidence: 90%
“…Recent literature emphasises the importance of empowerment in helping patients take charge of their own life and making decisions on their own (Grealish, Tai, Hunter, & Morrison, 2011). This is in line with the present study where the experience of being listened to and being able to talk about their experiences is viewed by patients as being positive and helpful in the healing process.…”
Section: Knowledge and Educationsupporting
confidence: 90%
“…This is consistent with previous research which has suggested that mental health patients find a lack of explanation of decision outcomes to be disempowering (Grealish et al, 2011;Tee et al, 2007) and a source of uncertainity (Rapport et al, 2010). We also found that mental health patients often wanted to have a more collaborative role, which is consistent with previous research that has suggested that mental health patients value the opportunity to negotiate their care (Hopkins and Niemiec, 2007) and derive increased confidence from involvement in treatment decisions (O'Toole et al, 2004), which can lead to the development of a sense of empowerment (Elstad and Eide, 2009).…”
Section: Comparison With Other Studiessupporting
confidence: 94%
“…Communication was enhanced when patients felt comfortable with and trusted their practitioners [22353943546267]. The development of trust required time, and was hampered by lack of continuity of practitioners [35445867].…”
Section: Resultsmentioning
confidence: 99%
“…Patients and families emphasised their individual strengths and capabilities, particularly their expertise about the disease and its management [436568]. Where practitioners did not recognise and value this expertise, participants felt that they were not being taken seriously [4352].…”
Section: Resultsmentioning
confidence: 99%